PENGARUH PEMBERIAN EDUKASI TERHADAP PENGETAHUAN DAN SIKAP BIDAN TENTANG TEKNIK SELF MANAJEMEN STRESS DALAM MENINGKATKAN KINERJA PELAYANAN KEBIDANAN - Kristanti, Helen; Lestari Nurul Aulia, Devy (Universitas Batam, 2025)
Stress among midwives can affect the quality of midwifery services, particularly in hospitals with high levels of activity. Education on stress management is a crucial effort to enhance midwives' knowledge and attitudes in providing optimal midwifery services. This study was conducted at RS Budi Kemuliaan Kota Batam, which includes various midwifery service units such as the 24/7 PONEK room, delivery room, midwifery clinic, postpartum room, and perinatal room. Each unit faces different work pressures, making stress management skills essential for midwives. The objective of this study was to determine the effect of education on midwives' knowledge and attitudes regarding stress management techniques. A pre-experimental design with a one-group pretest-posttest method was employed. The study sample consisted of 30 midwives, selected through total sampling. The instruments used were knowledge and attitude questionnaires, which were tested for validity and reliability. Data analysis included normality tests, which indicated normal distribution, followed by paired t-tests to assess the differences in knowledge and attitudes before and after the educational intervention. The results showed a significant improvement in midwives' knowledge and attitudes after the education (ρ-value < 0.05). The average knowledge score increased from 12.13 to 14.90, while the average attitude score increased from 13.10 to 16.00. The conclusion of this study is that education on stress management effectively enhances midwives' knowledge and attitudes. The practical implication is the need for regular education programs to support midwives' ability to manage stress, thereby continuously improving the quality of midwifery services.